Phytochemical screening of some antidysenteric medicinal plants of Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2014)
In this report, 40 antidysenteric medicinal plant species representing 24 families were considered for qualitative assessment of their secondary metabolites like alkaloids, flavonoids, glycosides, sterols and tannins. Alkaloids were present in all plant species, though in different degrees and the relative effectiveness of Dragendorffs reagent was better than others. Distribution of flavonoids, glycosides, sterols and tannins was sporadic in different plant species except A. cepa, A. marmelos, I. coccinea, M. indica, S. dulcis and Z. officinale, where all these metabolites were present. Abundance and mode of distribution of secondary metabolites in different test plants and their organs were discussed. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17850 J. Asiat. Soc. Bangladesh, Sci. 39(2): 139-146, December 2013